PENGEMBANGAN CAMPUS BASED CIVIC EDUCATION DI PERGURUAN TINGGI MUHAMMADIYAH - Tukiran Taniredja; Sri Harmianto; Eko Priyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2012)
This research aims, (1) create campus-based civic education Muhammadiyah University; (2) analyze the differences in democratic attitudes of students before and after instruction civic education; (3) analyze the relationship between the responses of students with learning PKn democratic manner after obtaining student learning civic education. Entire study population ivic education. lecturers and students at Muhammadiyah University of Central Java contracting Citizenship Education courses. Sampling technique with random sampling area. Faculty research sample civic education and college students Muhammadiyah University: Surakarta, Semarang, Magelang, Purworejo, and Purwokerto. Methods of data collection with the scale of attitude / opinioner, questionnaires, interviews and documentaries. Qualitative data, so have the meanings described a systematic and systemic, with the technique, data reduction, data display and conclusion. Before quantitative data were analyzed using statistical techniques, tested homoginitas and normality of data Results of data analysis to conclude (1) to create campus-based civic education is needed to Muhammadiyah University (a) the institution of a democratic institution that is anti-violence, constitutional and provide real benefits for the advancement of society; (b) The learning process is interactive, fun, challenging , motivate learners to participate actively, and to provide sufficient room for initiative, creativity, and independence, by placing the student as the subject of education, partners in the learning process, and as a congregation, members of the family, society and citizens, (c) learning is educative process, which occurs inside a critical discussion, analytical, inductive, deductive, and reflective through creative participatory dialogue, (2) there are significant differences in democratic attitudes of students before and after instruction civic education; (3) there was a significant relationship between responses civic education with students on learning of democratic attitudes of students after instruction civic education. Keywords: Civic Education, the campus-based civic education.